The prevalence of Salmonella spp. in working farm dogs and their home-kill raw meat diets in Manawatū, New Zealand. Issue 4 (4th July 2022) - Bojanić, K; Acke, E; Biggs, PJ; Midwinter, AC
ABSTRACT: Aims: To investigate the prevalence of Salmonella spp. in a convenience sample of working farm dogs and their home-kill raw meat diets in Manawatū, New Zealand. Methods: Fifty farms in the Manawatū, with at least three working/herding dogs per farm that were fed raw home-killed meat at least fortnightly, were visited. One sample of dog faeces and one sample of food were collected per farm using convenience sampling. If a dog did not defecate, a sample was obtained by digital recovery. Basic descriptive data for all dogs, meat and farm characteristics were recorded. Stomached meat samples and swabs from faecal samples were pre-enriched in buffered peptone water followed by two selective enrichments with agar subculture. Isolates were confirmed to be Salmonella spp. by serology and biochemical characterisation. Results: No Salmonella spp. were isolated from dog faeces or raw meat samples, giving an observed prevalence rate of 0 (95% CI = 0.0–7.1)%. Conclusions: In this study, there was no evidence that working farm dogs and their home-kill raw meat represent likely sources of infection with Salmonella spp. Clinical Relevance: Although this study found no evidence suggesting that farmers should change their feeding practices, it is based on a small sample, from a single region of New Zealand and involved sampling on one occasion for Salmonella spp. only. Currently, although the prevalence of Salmonella spp. carriage appears to be low, feeding raw meat-based diets to working dogs remains a risk and due to the potential zoonotic implications for humans, hygienic measures should be maintained when in contact with dogs and raw meat.